2019
DOI: 10.1111/jop.12825
|View full text |Cite
|
Sign up to set email alerts
|

Digital pathology: Review of current opportunities and challenges for oral pathologists

Abstract: Whole slide imaging (WSI) has impacted the practice of pathology in the arenas of education, clinical practice, and research. With digital slides, pathologists can circumvent the limitations of traditional glass. Presently, digital pathology is primarily utilized for second opinion consults, clinical conferences, and education at select academic medical centers, with its mainstream adoption on the rise. However, challenges of adoption for oral pathologists are unique given the highly specialized nature of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Advances in technology are now driving another major shift of current pathological paradigm towards digital. The practice of capturing static images of tissue sections or live stream a microscopic image using cameras was named digital pathology [ 16 ]. Recently, based on the development of modern computer and electronic systems, especially the advent of whole-slide imaging (WSI) technology, which enabled digitization of histological slides, the field of digital pathology has greatly evolved [ 17 ].…”
Section: The Development Of Pathologymentioning
confidence: 99%
“…Advances in technology are now driving another major shift of current pathological paradigm towards digital. The practice of capturing static images of tissue sections or live stream a microscopic image using cameras was named digital pathology [ 16 ]. Recently, based on the development of modern computer and electronic systems, especially the advent of whole-slide imaging (WSI) technology, which enabled digitization of histological slides, the field of digital pathology has greatly evolved [ 17 ].…”
Section: The Development Of Pathologymentioning
confidence: 99%
“…Perceptions regarding changes in traditional workflow following substantial capital expenditure requirements for the implementation of WSI systems are among the primary challenges to be overcome. [ 59 103 ] In addition, early studies have demonstrated decreased efficiency in signing out cases digitally due to the altered controls used for navigating through a slide. [ 26 ] However, there are indications to the contrary citing study design, level of experience looking at cases digitally, network speed, and workstation setup as factors contributing to improved diagnostic time.…”
Section: Discussionmentioning
confidence: 99%
“…[ 58 ] This expense is only further compounded by costs incurred through supplementary acquisition contracts (e.g., service agreements), staffing of additional personal (e.g., file clerks, system assistants), digital storage implementation, IT infrastructure, maintenance, training, hardware, and software integration expenses. [ 103 ] Return on investment is a primary concern in this regard. Many WSI devices included in our review have been featured in recent studies assessing benchmark metrics by which the overall efficiency, operational utility, and projected savings realized as a result of DP deployment within large anatomical departments are evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Digital pathology has made great strides in the past 20 years. A good review of challenges and advancements in digital pathology is provided in several publications [ 155 ]–[ 157 ]. Whole slide imaging is also now employed at some sites for primary anatomic pathology diagnostics.…”
Section: Processing Analysis and Understanding In Digital Pathologymentioning
confidence: 99%